Technical Appraisal of some Maize Shellers in Oyo and Kwara States of Nigeria - Omobowale, M. O.; Ogwumike, J. C.; Olenloa, A. E.; Kolayemi, O. R.; Ala, A. A.; Omodara, M. O.; Otitodun, G. O.; Nwaubani, S. I.; Ileleji, K. E.; McNeill, S. G.; Opit, G. P. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2022)
This study assessed the performance of some maize shellers in use in grain markets in Oyo and Kwara States, Nigeria. A preliminary survey conducted identified shellers in use as basic maize sheller (BMS) without blower, maize sheller with blower attachment (MSB) and the multi-purpose sheller (MPS). The shelling/cleaning performance of the shellers were assessed using yellow maize (SWAN 1 variety) and some key equipment parameters, which impact performance were measured. The air velocity for MSB and MPS ranged between 0.4 and 2.4 m/s which was not sufficient for efficient cleaning of chaff from shelled grains. Shaft speed for BMS, MSB and MPS were 845, 920 and 820 rpm, respectively. Average throughput for BMS, MSB and MPS was 1,714, 600 and 840 kg/hr, respectively with mean shelling efficiencies of 92.9, 82.7 and 97.9%, respectively. Mean cleaning efficiencies were 54.0 and 57.7% for MSB and MPS, respectively. The percentage grain loss for BMS, MSB and MPS were 17, 7.1 and 1.9%, respectively. It was observed that many fabricators do not consult agricultural engineers when producing machines, relying more on previous experience. Additionally, there was a lack of consideration for operator safety with the exposure of moving parts of the equipment in all the designs evaluated. A key recommendation from this study is that sheller designs should be standardized to ensure the provision of quality and highly efficient machinery for processors.